PENDAPATAN TENAGA KERJA KELUARGA PADA USAHA TERNAK SAPI POTONG DI KECAMATAN TOROH KABUPATEN GROBOGAN FAMILY LABOUR INCOME ON CATTLE FARMING IN TOROH SUBDISTRICT GROBOGAN REGENCY - Handayani, M.; Gayatri, S.; Mulyatno S, B. (Universitas Wahid Hasyim, 2005)
This research was done to know the family labour income on cattle farming compare to farmer wage in there and to know the rentability value compare to rate. Research was done in Juni ± Juli 2004. The method of this research was survey, collecting data was done by observation and direct interview. The research was done in Toroh subdistrict Grobogan Regency. Respondents were 52 farmers chose by stratified random sampling. There were three strata, the first were the farmers who had 1-2 cattle, second had 3-4 cattle and third had more than 4 cattle. Data was analyzed with descriptive. The results showed that the family labour income was higher than farmer wage. Family labour income in each stratum were Rp 13.790,67/man-days, Rp 15.966,29/ man-days and 13.278,95/ man-days respectively, while the farmer wage in there was Rp 12.600/ man-days. Rentability value was higher than rate. Rentability in each stratum were 27.61%, 23.74%, and 24.53% respectively, while the rate was 12.5%. The conclusion of this research was that the cattle farming in Toroh Subdistrict was prospectively. Keywords: family labour income, rentability value